Effect of strontium content on chromium deposition and poisoning in Ba1-xSrxCo0.8Fe0.2O3-δ (0.3≤ x ≤0.7) cathodes of solid oxide fuel cells - Kim, Y.; Chen, X.; Jiang, San Ping; Bae, J. (The Electrochemical Society, Inc, 2012)
The effect of strontium content on Cr deposition and poisoning in barium strontium cobalt ferrite electrodes, Ba1−xSrxCo0.8Fe0.2O3−δ (BSCF, 0.3 ≤ x ≤ 0.7), was investigated at 900°C for 20 h with a cathodic polarization of 200 mA cm−2. In contrast to the superb and stable electrochemical performance of the BSCF electrodes without interconnects, electrode polarization resistance and overpotential (RE and η) were found to increase for the O2 reduction reaction on BSCF electrodes in the presence of Fe-Cr metallic interconnects. Most important, the increase in RE and η values, ΔRE and Δη measured after polarized at 200 mA cm−2 for 20 h, increased significantly as the Sr content of the BSCF electrodes was increased, indicating that the Sr content in BSCF electrodes is a governing factor in Cr poisoning. Scanning electron microscopy (SEM) analysis of the BSCF electrodes after the Cr poisoning test at 900°C for 20 h revealed the presence of Cr deposits on the cathode surface. The magnitude of Cr deposits on the electrode surface under the rib of the interconnect is significantly higher than that under the channel of the interconnect. The results in this study indicate that Sr and/or Ba segregation plays an important role in the Cr deposition and poisoning for the O2 reduction on BSCF cathodes, which is closely related to the Ba/Sr ratio of the cathode.